Pemanfaatan Media Video Untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran Aqidah Akhlak Kelas V MI - Fatmawati Norma Sari (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2023)
The purpose of this study was to find out the activities and learning outcomes of students regarding the use of video as a learning medium in the subject of Akita Akhlak. The use of learning media using lecture media and book packages, results in a lack of activity and a low value of the Akhlak Aqidah below the average set by the school. Based on the existing problems from the results of observations and interviews conducted with teachers and students, a research was carried out using video as a learning medium. This research was conducted using an experimental method with the design of Pretest – Posttest Technological Pedagogical Content Knowledge. The results showed that the effect of using video as a learning medium was higher than lecture learning media and using book packages on student learning activities and outcomes